The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
All Days 2010
DOI: 10.2118/132513-ms
|View full text |Cite
|
Sign up to set email alerts
|

Application of Lithofacies Models to Characterize Unconventional Shale Gas Reservoirs and Identify Optimal Completion Intervals

Abstract: Unconventional shale gas reservoirs are economically viable hydrocarbon prospects, and their development has rapidly increased in North America. These reservoirs must be routinely drilled horizontally and hydraulically fracture stimulated to maximize production rates. Identification of the different chemostratigraphic units or lithofacies that make up these reservoirs is crucial for devising completion strategies because some lithofacies are more favorable to gas recovery due to their organic content and geome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Kommugudem Formation on basis of mineralogy indicates similar composition as brittle zones of the Barnett Shale Formation (Figure 11a,b). The Barnett Shale consists of 20.0 to 80.0% quartz with a wide range of mineralogical variation resulting in seven different lithofacies, while Kommugudem Formation has quartz ranging from 40.97 to 91.19% (Loucks & Ruppel, 2007; Mitra, Warrington, & Sommer, 2010). A further similarity is explored based on the form of minerals, which is governed by post‐depositional alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Kommugudem Formation on basis of mineralogy indicates similar composition as brittle zones of the Barnett Shale Formation (Figure 11a,b). The Barnett Shale consists of 20.0 to 80.0% quartz with a wide range of mineralogical variation resulting in seven different lithofacies, while Kommugudem Formation has quartz ranging from 40.97 to 91.19% (Loucks & Ruppel, 2007; Mitra, Warrington, & Sommer, 2010). A further similarity is explored based on the form of minerals, which is governed by post‐depositional alterations.…”
Section: Discussionmentioning
confidence: 99%
“…The transgressive systems tract represents high TOC and pyrite contents with high porosity. The abundance of pyrite influences brittleness, and therefore affects the completion quality and reservoir reserve estimates [34].…”
Section: Sequence Stratigraphic Interpretation Of Horn River Formatio...mentioning
confidence: 99%
“…In terms of petrological research, comprehensive investigations have been carried out using core descriptions, thin section analysis, scanning electron microscopy, and X-ray diffraction analysis. At the same time, the heterogeneity of different types of shale lithofacies is reflected in its sedimentary structure (lamina and paleontology), organic matter content, and diagenesis (Surdam and Stanley, 1979;Bohacs et al, 2000;Loucks et al, 2007;Mitra et al, 2010;Xu et al, 2020a). Studies on the lacustrine shale of the Shahejie Formation in the Bohai Bay Basin have revealed that its lithofacies is divided into felsic shale, mixed shale, dolomite and carbonate shale, and massive, layered, and laminar shale (Ma et al, 2017;Bai et al, 2020;Li M. et al, 2020;Wu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%